Preparation method of iodine-doped titanium dioxide visible light photocatalyst
By using potassium titanium oxalate and sodium periodate under acidic conditions, the problem of limited application range of TiO2 in visible light is solved, and efficient visible light photocatalytic performance and good stability are achieved.
Patent Information
- Application Number
- CN202411552061.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-04-04
AI Technical Summary
The existing TiO2 photocatalysts have limited application ranges in visible light, resulting in limited practical applications in environmental restoration.
Iodine-doped titanium dioxide (I-TiO2) visible light photocatalyst was prepared by hydrothermal under acidic conditions using potassium titanium oxalate and sodium periodate as raw materials.
The photoresponse range of titanium dioxide has been broadened and its photocatalytic performance under visible light has been improved. After three cycles, the photocatalytic degradation rate is still higher than 80%, which has the advantages of being efficient, simple and economical.
Smart Images

Figure CN119746839A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional materials and textile printing and dyeing industry, and specifically relates to a method for preparing an iodine-doped titanium dioxide visible light photocatalyst. Background Art
[0002] Semiconductor photocatalytic technology has opened up a new way for wastewater treatment. Compared with traditional water treatment, photocatalytic technology has the advantages of mild use conditions, simplicity and high efficiency. Among many different photocatalysts, TiO2 has been studied most extensively because it has strong oxidation ability, can decompose organic pollutants, is non-toxic, has super hydrophilicity, high durability, chemical stability, and low cost. However, it has problems such as limited application range under visible light. Therefore, research related to TiO2 modification is still a major challenge in the field of environmental remediation.
[0003] Since the research of photocatalysts involves multiple disciplines such as catalysis, materials, photochemistry, and environment, it is quite difficult. Although a lot of research has been done at home and abroad to improve the activity and stability of photocatalysts, and great progress has been made, there is still a certain distance from practical application. Therefore, if photocatalysis and photocatalytic processes are to be truly applied in real life, a lot of research work needs to be continued in improving the activity and stability of catalysts. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing an iodine-doped titanium dioxide visible light photocatalyst.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0008] Potassium titanium oxalate was dissolved in deionized water and stirred to obtain solution Ⅰ;
[0009] Sodium periodate was added to solution I, sulfuric acid was added dropwise, and the mixture was mixed to obtain solution II;
[0010] Solution II was subjected to hydrothermal reaction, and then washed with water, freeze-dried, and ground to obtain iodine-doped titanium dioxide visible light photocatalyst.
[0011] As a preferred embodiment of the method for preparing the iodine-doped titanium dioxide visible light photocatalyst of the present invention, the concentration of the sodium periodate is 0.14-0.26 mol / L, and the molar ratio of the sodium periodate to potassium titanium oxalate is 5:7-13.
[0012] As a preferred embodiment of the method for preparing the iodine-doped titanium dioxide visible light photocatalyst of the present invention, the concentration of the potassium titanium oxalate is 0.1-0.5 mol / L.
[0013] As a preferred embodiment of the method for preparing the iodine-doped titanium dioxide visible light photocatalyst of the present invention, the concentration of the sulfuric acid is 60-65%, and the volume ratio of the sulfuric acid to solution I is 1-4:100.
[0014] As a preferred embodiment of the method for preparing iodine-doped titanium dioxide visible light photocatalyst of the present invention, the stirring time is 20 to 30 minutes.
[0015] As a preferred embodiment of the method for preparing the iodine-doped titanium dioxide visible light photocatalyst of the present invention, the temperature of the hydrothermal reaction is 140-180°C.
[0016] As a preferred embodiment of the method for preparing the iodine-doped titanium dioxide visible light photocatalyst of the present invention, the time of the hydrothermal reaction is 10 to 12 hours.
[0017] As a preferred embodiment of the method for preparing iodine-doped titanium dioxide visible light photocatalyst of the present invention, the freeze-drying temperature is -70 to -90°C.
[0018] As a preferred embodiment of the method for preparing the iodine-doped titanium dioxide visible light photocatalyst of the present invention, the freeze-drying time is 5 to 8 hours.
[0019] As a preferred solution of the method for preparing the iodine-doped titanium dioxide visible light photocatalyst of the present invention, the photocatalytic degradation rate of the iodine-doped titanium dioxide visible light photocatalyst is still higher than 80% after being recycled for 3 times.
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention selects potassium titanium oxalate as a titanium source and sodium periodate as an oxidant and an iodine source, reacts under acidic conditions, and adopts a hydrothermal method to prepare an iodine-doped titanium dioxide (I-TiO2) visible light photocatalyst, which broadens the light response range of titanium dioxide and has good visible light photocatalytic performance. After being recycled for three times, the photocatalytic degradation rate is higher than 80%, which has the advantages of high efficiency, simplicity, and economy.
[0022] (2) The present invention investigates the catalytic performance of the photocatalyst under different sodium periodate addition amounts and obtains the optimal addition amount.
[0023] (3) The present invention investigates the catalytic performance of iodine-doped titanium dioxide visible light photocatalysts after adding different scavengers, and reveals that the importance of each free radical in the I-TiO2 photocatalytic reaction is as follows: - >h + >·OH. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0025] Figure 1 This is the XRD spectrum of I-TiO2 in Example 1 of the present invention.
[0026] Figure 2 This is a SEM photograph of I-TiO2 in Example 1 of the present invention.
[0027] Figure 3 The UV-visible absorption spectra of I-TiO2 and P25 in Example 1 and Comparative Example 1 of the present invention are shown.
[0028] Figure 4 This is a graph showing the photocatalytic degradation rate of MO solution by I-TiO2 under visible light irradiation in Examples 1 and 2 of the present invention.
[0029] Figure 5 This is a graph showing the cyclic photocatalytic degradation rate of I-TiO2-9 to MO solution under visible light irradiation in Example 2 of the present invention.
[0030] Figure 6 This is a graph showing the photocatalytic degradation rate of I-TiO2 to MO solution when different free radical scavengers are added under visible light irradiation in Example 3 of the present invention. DETAILED DESCRIPTION
[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0032] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0033] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0034] The photocatalytic performance testing method of the catalyst in the present invention is:
[0035] The photocatalytic performance of I-TiO2 was tested by photocatalytic degradation experiments under simulated ultraviolet visible light (300W xenon lamp). 0.1g of the sample was dispersed in 100mL of 10mg / L methyl orange (MO) solution. After magnetic stirring for 30min in the dark to reach adsorption-desorption equilibrium, the solution was irradiated under a xenon lamp. Every 10min, about 2mL of the solution was centrifuged, and the upper clear liquid was taken to measure its absorbance at the maximum absorption peak of 463nm. The calculation of the photocatalytic degradation rate of the MO solution is shown in formula (1):
[0036]
[0037] Wherein, η—degradation rate (%);
[0038] A0—absorbance of MO solution before illumination;
[0039] A t —Absorbance of MO solution after t hours of illumination.
[0040] The free radical capture experimental method in the present invention is:
[0041] In a typical photocatalytic degradation reaction, the main active components are O2 - , OH and h + Etc. Therefore, detecting the active species that play a leading role in the photocatalytic system is essential to reveal the photocatalytic degradation mechanism. Different free radical quenchers were added to the photocatalytic degradation reaction mixture to study its main active components.
[0042] Add 1 mL of p-benzoquinone solution, disodium ethylenediaminetetraacetate solution and isopropanol solution respectively to a mixed solution containing 0.1 g of I-TiO2 and 100 mL of 10 mg / L MO. After magnetic stirring for 30 minutes in a dark place, irradiate under simulated ultraviolet-visible light (300 W xenon lamp). After 60 minutes, take the solution, centrifuge it, take the supernatant to test the absorbance and analyze it.
[0043] The calculation of the absorption coefficient of the catalyst in the present invention is shown in formula (2):
[0044] αhv=A(hv-Eg)n / 2 (2)
[0045] Where α is the absorption coefficient, h is Planck's constant, v is the frequency, A is the proportional constant of the semiconductor catalyst, and Eg is the bandgap width. The value of n depends on the type of interband transition of the catalyst. The value of n is 2 for direct transition and 4 for indirect transition. TiO2 is an indirect transition semiconductor material, so n is 4. Substituting into the formula, we get hv~(ahv) 1 / 2 The bandgap width can be obtained based on the intercept of the curve.
[0046] Example 1
[0047] This embodiment provides a method for preparing an iodine-doped titanium dioxide visible light photocatalyst, specifically:
[0048] Potassium titanium oxalate was added into deionized water and stirred to obtain solution I, wherein the concentration of potassium titanium oxalate was 0.1 mol / L;
[0049] Sodium periodate was added to the mixed solution 1, the concentration of sodium periodate was 0.18 mol / L, and the mixture was stirred. 0.75 mL of 65% sulfuric acid was added dropwise, and the mixture was stirred to obtain solution II.
[0050] Solution II was transferred to a 150 mL polytetrafluoroethylene-lined stainless steel reactor for hydrothermal reaction at a temperature of 150°C for 12 h, and then naturally cooled to room temperature to obtain a light yellow solid.
[0051] The product was washed with water, freeze-dried at -85°C for 7 h, and ground to obtain an iodine-doped titanium dioxide visible light photocatalyst.
[0052] The prepared photocatalyst was recorded as I-TiO2-9.
[0053] X Pert3 PRO X-ray diffractometer (XRD) was used to test the phase composition, crystal form, particle size, crystallinity and other information of the samples, and the scanning angle 2θ was 10° to 80°. Figure 1 This is the XRD spectrum of I-TiO2. It can be seen that I-TiO2 has obvious diffraction peaks at 2θ of 25.26°, 37.92°, 48.08°, 54.26°, 62.78°, 69.14° and 74.94°. The crystal planes corresponding to the XRD standard card (PDF#89-4921) are (101), (004)(200), (105), (204), (116) and (215). These diffraction peaks are characteristic peaks of anatase.
[0054] Figure 2The scanning electron micrographs of I-TiO2 are (a) × 100,000, (b) × 50,000, (c) × 25,000, and (d) × 10,000. It can be seen that the I-TiO2 nanoparticles are spherical and have obvious aggregation. This agglomeration occurs at the contact between particles during the drying process. Factors such as Brownian motion, hydrodynamic effects, and capillary resistance also contribute to the agglomeration behavior during the drying stage. The diameter of the I-TiO2 crystals is in the range of 7-10nm.
[0055] Comparative Example 1
[0056] This comparative example uses P25 for comparison with I-TiO2-9 in Example 1. P25 is a titanium dioxide of a mixed phase of anatase crystal and rutile crystal with an average particle size of 25 nm, wherein the anatase phase accounts for about 80% and the rutile phase accounts for about 20%.
[0057] Figure 3 The UV-visible absorption spectra of I-TiO2 and P25 in Example 1 are shown. It can be seen that the light absorption of I-TiO2 in the visible light region is significantly stronger than that of P25 powder, and P25 has basically no absorption of light in the visible light region. The corresponding bandgap widths of I-TiO2 and P25 are 3.05eV and 3.15eV respectively.
[0058] Example 2
[0059] The difference between this embodiment and embodiment 1 is that the addition amount of sodium periodate is adjusted to 7, 10, and 11 mmol, and the concentrations are 0.14, 0.2, and 0.22 mol / L, respectively. The other operating steps are the same as those in embodiment 1, and the prepared photocatalysts are respectively recorded as I-TiO2-7, I-TiO2-10, and I-TiO2-11.
[0060] Figure 4 The photocatalytic activity degradation curve of I-TiO2 photocatalyst prepared with different amounts of sodium periodate added in Examples 1 and 2 under visible light irradiation. Titanium dioxide responds in the ultraviolet region and has a low utilization rate of sunlight. Figure 4 It can be seen that iodine-doped titanium dioxide broadens the light response range of titanium dioxide and improves its photocatalytic effect. The photocatalytic rates are I-TiO2-9>I-TiO2-7>I-TiO2-10>I-TiO2-11. Among them, I-TiO2-9 has the fastest photodegradation rate, and the degradation rate can reach 89.65% in 60 minutes.
[0061] The photocatalytic stability data of photocatalysts I-TiO2-9, I-TiO2-7, I-TiO2-10, and I-TiO2-11 are shown in Table 1. Figure 5This is the cyclic photocatalytic degradation rate diagram of I-TiO2-9 on MO solution under visible light irradiation.
[0062] Table 1 Comparison of photocatalytic stability of different photocatalysts
[0063]
[0064] From Table 1 and Figure 5 It can be seen that I-TiO2-9 has the best cyclic photocatalytic degradation effect and the best stability. After three cycles of use, the photocatalytic degradation rate is higher than 80%.
[0065] Example 3
[0066] This example explores the catalytic performance of the photocatalyst I-TiO2 after adding different capture agents, conducts active group capture experiments, and further studies the photocatalytic mechanism of I-TiO2. This example uses the catalyst I-TiO2-9 prepared in Example 1.
[0067] Figure 6 The photocatalytic degradation rate of I-TiO2 to MO solution when different free radical scavengers were added under visible light irradiation. It can be seen that the addition of isopropanol, p-benzoquinone and disodium ethylenediaminetetraacetic acid reduced the photocatalytic degradation rate of I-TiO2 to MO solution to varying degrees. With the addition of p-benzoquinone, the degradation rate of MO solution dropped sharply, indicating that·O2 - It is the main active component in the system. At the same time, the addition of isopropanol and disodium ethylenediaminetetraacetate also reduced the degradation rate of MO solution, indicating that ·OH and h + It also plays a role in the I-TiO2 photocatalytic degradation of MO system. According to the degree of inhibition of the photocatalytic degradation activity by different free radical scavengers, the importance of each free radical in the I-TiO2 photocatalytic reaction is as follows: - >h + >·OH.
[0068] Comparative Example 2
[0069] This comparative example uses pure TiO2 to compare with the catalysts of Examples 1 and 2.
[0070] Pure TiO2 has no photocatalytic effect under visible light irradiation. Compared with the photocatalysts in Examples 1 and 2, pure TiO2 has a wider bandgap and can only absorb ultraviolet light, and its utilization rate of sunlight is not high. The I-TiO2 in the example has been modified and improved to address the problems of pure TiO2, so that it can respond under visible light.
[0071] Comparative Example 3
[0072] The difference between this comparative example and Example 1 is that the addition amount of sodium periodate is adjusted to 5 mmol, and the other operating steps are the same as those in Example 1. The prepared photocatalyst is recorded as I-TiO2-5.
[0073] The sample was subjected to photocatalytic testing and it was found that it had basically no degradation effect, which suggests that the doping modification was unsuccessful.
[0074] In summary, the present invention selects potassium titanium oxalate as the titanium source and sodium periodate as the oxidant, reacts under acidic conditions, and uses a hydrothermal method to prepare iodine-doped titanium dioxide (I-TiO2) visible light photocatalyst, which broadens the light response range of titanium dioxide and has good visible light photocatalytic performance. After recycling for 3 times, the photocatalytic degradation rate is higher than 80%, and it has the advantages of high efficiency, simplicity, and economy. The present invention explores the catalytic performance of the photocatalyst under different sodium periodate addition amounts and obtains the optimal addition amount; explores the catalytic performance of the iodine-doped titanium dioxide visible light photocatalyst after adding different scavengers, and reveals that the importance of each free radical in the I-TiO2 photocatalytic reaction process is as follows: ·O2 - >h + >·OH.
[0075] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing an iodine-doped titanium dioxide visible light photocatalyst, characterized in that: include, Potassium titanium oxalate was dissolved in deionized water and stirred to obtain solution Ⅰ; Sodium periodate was added to solution I, sulfuric acid was added dropwise, and the mixture was mixed to obtain solution II; Solution II was subjected to hydrothermal reaction, and then washed with water, freeze-dried, and ground to obtain iodine-doped titanium dioxide visible light photocatalyst.
2. The method for preparing the iodine-doped titanium dioxide visible light photocatalyst according to claim 1, characterized in that: The concentration of the sodium periodate is 0.14-0.26 mol / L, and the molar ratio of the sodium periodate to potassium titanium oxalate is 5:7-13.
3. The method for preparing the iodine-doped titanium dioxide visible light photocatalyst according to claim 2, characterized in that: The concentration of the potassium titanium oxalate is 0.1-0.5 mol / L.
4. The method for preparing the iodine-doped titanium dioxide visible light photocatalyst according to claim 1, characterized in that: The concentration of the sulfuric acid is 60-65%, and the volume ratio of the sulfuric acid to solution I is 1-4:
100.
5. The method for preparing iodine-doped titanium dioxide visible light photocatalyst according to claim 1, characterized in that: The stirring time is 20 to 30 minutes.
6. The method for preparing iodine-doped titanium dioxide visible light photocatalyst according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 140-180°C.
7. The method for preparing iodine-doped titanium dioxide visible light photocatalyst according to claim 6, characterized in that: The hydrothermal reaction time is 10 to 12 hours.
8. The method for preparing an iodine-doped titanium dioxide visible light photocatalyst according to claim 1, characterized in that: The freeze-drying temperature is -70 to -90°C.
9. The method for preparing iodine-doped titanium dioxide visible light photocatalyst according to claim 8, characterized in that: The freeze-drying time is 5 to 8 hours.
10. The method for preparing the iodine-doped titanium dioxide visible light photocatalyst according to claim 9, characterized in that: After the iodine-doped titanium dioxide visible light photocatalyst is recycled for 3 times, the photocatalytic degradation rate is still higher than 80%.
Citation Information
Patent Citations
Method for preparing photocatalyst doping with mesopore nanometer titanium oxide
CN101204648A
Highly pure brookite type titanium dioxide nanosheet, and preparation method and application thereof
CN104211109A
Preparation method of copper / titanium dioxide composite photocatalytic material
CN109865514A